The Bejeleng Tradition: Integrating Indigenous Spirituality into Lombok's Cultural Tourism Strategy - S. Ali Jadid Al Idrus; Prosmala Hadisaputra; Lenny Herlina (Universitas Islam Negeri Madura, 2026)
The growth of cultural tourism has intensified debates on authenticity, sustainability, and the ethical integration of indigenous practices into tourism development. In East Lombok, the Bejeleng traditionl”a sacred Sasak ritual associated with the production of traditional coconut oil (minyak Jeleng) embodies these tensions because it is governed by strict spiritual regulations, collective participation, and ritual purity. This study examines how Bejeleng can be strategically integrated into Lombok's cultural tourism development without compromising its spiritual integrity. Grounded in Greg Richards cultural tourism framework, the study employs a qualitative phenomenological approach to understand indigenous spirituality as a collective social experience. Data were collected through participant observation, in-depth interviews with religious leaders and ritual participants, and documentary analysis, and were analyzed through a two-stage thematic procedure combining inductive, participant-driven open coding with theoretically informed deductive interpretation based on Richards cultural tourism framework. The findings show that integrating Bejeleng into cultural tourism must be selective, value-based, and community-led. Indigenous spirituality functions as a non-negotiable boundary against ritual commodification, while community leadership regulates external engagement. Tourist involvement is limited to non-ritual domains, including observation and the use of ritual-derived products, whereas economic benefits remain controlled secondary outcomes that do not alter ritual practices. This study contributes to cultural tourism scholarship by extending Richards framework to sacred ritual production processes and demonstrating that meaningful cultural experiences can be constructed through symbolic proximity rather than direct participation.